2003
DOI: 10.1258/000456303321610501
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temporal variation in biochemical markers of trisomy 21 across the first and second trimesters of pregnancy on the estimation of individual patient-specific risks and detection rates for Down's syndrome

Abstract: Background In a previous study we examined the changes in the median multiple of the median (MoM) with gestation of free beta human chorionic gonadotrophin (FbhCG), total human chorionic gonadotrophin (ThCG), a-fetoprotein (AFP) and pregnancy-associated plasma protein A (PAPP-A) in a large series of Down's syndrome pregnancies. Results showed that there was a significant temporal variation of the MoM for each marker. In this paper, we assess the impact of this temporal shift on the estimation of patient-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
(26 reference statements)
4
33
0
2
Order By: Relevance
“…The low ADAM12 results confirm the early observations of Laigaard et al [17] who demonstrated in a small series of 10 cases that prior to 55 days, levels of ADAM12 were less than the detection limit of the assay and increased as the gestational age increased. This mirrors the temporal pattern that has been described for ADAM12 in pregnancies with trisomy 21 [19,20], and is similar to that described for PAPP-A [31,32], which like ADAM12 is another IGFBP protease [13,33]. However the temporal pattern is unlike that seen for PAPP-A in trisomy 18 when the low levels of PAPP-A in the first trimester are even further reduced in the second trimester [6,34,35].…”
Section: Discussionsupporting
confidence: 84%
“…The low ADAM12 results confirm the early observations of Laigaard et al [17] who demonstrated in a small series of 10 cases that prior to 55 days, levels of ADAM12 were less than the detection limit of the assay and increased as the gestational age increased. This mirrors the temporal pattern that has been described for ADAM12 in pregnancies with trisomy 21 [19,20], and is similar to that described for PAPP-A [31,32], which like ADAM12 is another IGFBP protease [13,33]. However the temporal pattern is unlike that seen for PAPP-A in trisomy 18 when the low levels of PAPP-A in the first trimester are even further reduced in the second trimester [6,34,35].…”
Section: Discussionsupporting
confidence: 84%
“…Because NT measurements are not involved, the lower gestational age limit for the first-trimester sample collection can be earlier than 11 weeks' gestation, a time when PAPP-A measurements are more discriminatory. 70 However, laboratories would need to obtain appropriate Down syndrome risk equations and develop reliable median levels before offering the test clinically. Another issue is whether to accept samples that are dated by LMP.…”
Section: Serum Integrated Screening (Nt Measurements Not Available)mentioning
confidence: 99%
“…Existe una significativa variación temporal de los MoM de los marcadores bioquímicos usados en el cribado de SD a lo largo de la gestación 20,21 , lo cual hace que cada marcador tenga un perfil de eficacia distinto en cada momento de la gestación. Por ello, cuando se usan varios marcadores, se debe elegir el periodo de tiempo ideal en el que su determinación conjunta aumente su eficacia.…”
Section: Discussionunclassified